(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Learning a foreign language contributes to the development of cognitive functions of the human psyche. In the process of mastering a foreign language practicing different memorization techniques, formed philological thinking, expand knowledge of reality. Especially reading helps to develop all these skills. At the initial stage of learning reading comes to master the technique of reading aloud, and only to some extent, self-reading. As reading is one of the most important means of obtaining information and it has a significant place in the life of an educated person, this article deals with the role of reading in the process of teaching the foreign language.